1992
DOI: 10.1111/j.2044-8341.1992.tb01692.x
|View full text |Cite
|
Sign up to set email alerts
|

The belief in the transmigration of souls: Psychotherapy of a Druze patient with severe anxiety reaction

Abstract: In this paper the culture-sensitive psychotherapy of a 19-year-old Druze patient with severe anxiety reaction is described. The patient explained his anxiety and his symptoms as stemming from violent death in his former life and subsequent transmigration. The therapists joined the patient's explanatory model and previous traditional healing, adding hypnotic suggestion which relieved the symptoms. The relationship of patient symptomatology to cultural background, multiple personality disorder, possession and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 3 publications
1
27
0
1
Order By: Relevance
“…Believers maintain that when a Druze dies, the soul is immediately reborn in another Druze body, or reborn beyond the human realm into the next ascending realm of closeness to God (Bennet, 2006). Unlike Hindu or Buddhist ideas, subsequent lives are not seen as dependent on action in past lives or as going in a particular direction (Daie, Witztum, Mark, & Rabinovitz, 1992). The physical body is seen as a temporary vehicle for the eternal soul.…”
Section: The Belief In Reincarnationmentioning
confidence: 99%
See 1 more Smart Citation
“…Believers maintain that when a Druze dies, the soul is immediately reborn in another Druze body, or reborn beyond the human realm into the next ascending realm of closeness to God (Bennet, 2006). Unlike Hindu or Buddhist ideas, subsequent lives are not seen as dependent on action in past lives or as going in a particular direction (Daie, Witztum, Mark, & Rabinovitz, 1992). The physical body is seen as a temporary vehicle for the eternal soul.…”
Section: The Belief In Reincarnationmentioning
confidence: 99%
“…One of the traditions that has helped the Druze survive as a group is probably their loyalty to the state in which they reside. Thus, Syrian Druze identify themselves with the goals of Syria, while most Israeli Druze men serve in the Israel Defense Force and identify with Israeli causes (Daie et al, 1992). Many Druze are convinced that the belief in the transmigration of souls is useful in leading to fearlessness in battle and quote a Druze battle cry, ''Tonight my mother's womb'' (I'll be killed in battle today, but I shall be instantly reincarnated), which may go some way toward explaining the ferociousness of the Druze in war (Fisk, 1992;Littlewood, 2001).…”
Section: The Druzementioning
confidence: 99%
“…Developing countries are not the exclusive terrain of possession disorders and exorcism practices. Reports on these conditions were based on observations from countries in North America [63][64][65] and Latin America [66], the United Kingdom [67], Switzerland [68], Italy [69], France [70], Greece [71], Israel [30,72,73], Korea [74], and Russia [75]. A Barna Research poll showed that 54% of adult Americans believe that ''a human being can be under the control or the influence of spiritual forces such as demons'' [76].…”
Section: Possession Trance and Religionmentioning
confidence: 99%
“…Transmigration of the soul is a basic tenet of both Hinduism and Buddhism, which teach that the soul of every person and plant is eternal and returns after death in another form. The concept is also found in divergent schools of Judaism and in various sects of Islam, especially the Alawites and the Druze [5].…”
Section: Introductionmentioning
confidence: 99%